Biliary cystadenoma in a child: A rare entity - Sohail Ahmad; Subrat Kumar Sahoo; Aditya Arvind Manekar; Janjala Narahari; Bikasha Bihary Tripathy; Mukund Sable; Manoj Kumar Mohanty (Wolters Kluwer Medknow Publications, 2023)
Biliary cystadenoma, a rare potentially malignant hepatic cystic lesion, is characterized by multiloculations and septations. It is common in middle-aged females (about 5% of nonparasitic liver cysts); only 12 cases are described in children. We report a rare case of hepatic biliary cystadenoma in a 3-year-old girl, with a gradually increasing lump in the right upper abdomen. Complete excision with a healthy liver margin was done.